2003
DOI: 10.1111/1467-7717.00216
|View full text |Cite
|
Sign up to set email alerts
|

Planning STI/HIV Prevention Among Refugees and Mobile Populations: Situation Assessment of Sudanese Refugees

Abstract: This article reflects an investigation of knowledge, attitudes and behaviours and HIV/STI prevalence of Sudanese refugees and Ethiopian sex workers in 1992. It represents one of the earliest such investigations within an African refugee population. The investigation took place in the Dimma refugee settlement in south-western Ethiopia and study participants included Sudanese refugee men and women and Ethiopian female sex workers. Methods used for this investigation included focus group discussions, behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
(6 reference statements)
3
19
0
Order By: Relevance
“…One would expect a population living in the U.S. to have greater access to education on HIV prevention, and therefore greater knowledge, different attitudes and beliefs, and altered sexual behavior from their counterparts in their country of origin. However, the results of this study revealed that knowledge, attitudes, beliefs, and behaviors toward HIV infection are nearly the same as previous studies doing similar assessments in Sudan (Ali et al, 2001;Holt et al, 2003;Wilson and Mehryar, 1991). Nearly all participants in our study responded that they had heard of HIV.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One would expect a population living in the U.S. to have greater access to education on HIV prevention, and therefore greater knowledge, different attitudes and beliefs, and altered sexual behavior from their counterparts in their country of origin. However, the results of this study revealed that knowledge, attitudes, beliefs, and behaviors toward HIV infection are nearly the same as previous studies doing similar assessments in Sudan (Ali et al, 2001;Holt et al, 2003;Wilson and Mehryar, 1991). Nearly all participants in our study responded that they had heard of HIV.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, this is the first study to evaluate any Sudanese population in the U.S. (Ali et al, 2001;Holt et al, 2003;Wilson and Mehryar, 1991). The prior studies conducted in Sudan demonstrated that high sexual risk behavior was more prevalent in refugee populations, with single males emerging as a priority group for prevention interventions (Ali et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 27 articles mentioning factors impeding HIV/AIDS health services and risks of HIV/AIDS infection in cross-national migrants 31,34–36,3860. Some articles specifically reported the situation of migrants in certain regions, ie, Asia,34,35,44–47,51,59,60 America (particularly among Mexican migrants),40,42,43,45,48,53 and Africa 31,38,41,49,52.…”
Section: Resultsmentioning
confidence: 99%
“…Sudan is North Africa and the Middle East region's worst HIV-affected country [9,13,21,22]. The prevalence of HIV infection in Sudan was estimated at 1.6% in 2005, representing nearly 80% of HIV cases in the region [12,22].…”
Section: Introductionmentioning
confidence: 99%